Neonatal Vitamin C and Cysteine Deficiencies Program Adult Hepatic Glutathione and Specific Activities of Glucokinase, Phosphofructokinase, and Acetyl-CoA Carboxylase in Guinea Pigs' Livers - Vitor Teixeira; Ibrahim Mohamed; Jean-Claude Lavoie (MDPI AG, 2021)
Premature neonates are submitted to an early-life oxidative stress from parenteral nutrition, which is vitamin C (VC) deficient and induces low endogenous levels of glutathione. The oxidative stress caused by these deficiencies may permanently affect liver glycolysis and lipogenesis. This study evaluates the short- and long-term effects of neonatal VC and cysteine deficient diets on redox and energy metabolism. Three-day-old Hartley guinea pigs from both sexes were given a regular or a deficient diet (VC, cysteine, or both) until week 1 of life. Half of the animals were sacrificed at this age, while the other half ate a complete diet until 12 weeks. Liver glutathione and the activity and protein levels of glucokinase, phosphofructokinase, and acetyl-CoA-carboxylase were measured. Statistics: factorial ANOVA (5% threshold). At 1 week, all deficient diets decreased glutathione and the protein levels of glucokinase and phosphofructokinase, while cysteine deficiency decreased acetyl-CoA-carboxylase levels. A similar enzyme level was observed in control animals at 12 weeks. At this age, VC deficiency decreased glutathione, while cysteine increased it. Acetyl-CoA-carboxylase protein levels were increased, which decreased its specific activity. Early-life VC and cysteine deficiencies induce neonatal oxidative stress and an adult-like metabolism, while predisposing to increased lipogenic rates during adulthood.